2021
DOI: 10.3390/app112210755
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PM2.5 in Seoul, Korea Estimated from the Various Ground-Based and Satellite AOD

Abstract: Based on multiple linear regression (MLR) models, we estimated the PM2.5 at Seoul using a number of aerosol optical depth (AOD) values obtained from ground-based and satellite remote sensing observations. To construct the MLR model, we consider various parameters related to the ambient meteorology and air quality. In general, all AOD values resulted in the high quality of PM2.5 estimation through the MLR method: mostly correlation coefficients >~0.8. Among various polar-orbit satellite AODs, AOD values from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…In winter, the correlation coefficients between AOD and PM 2.5 and AQI were the lowest, at 0.46 and 0.48, respectively. This result is consistent with the findings of many existing studies [34,60]. It also means that the correlation between AOD and AQI was higher than that of PM 2.5 in autumn and winter.…”
Section: Relationship Between Aod and Pm 25 /Aqisupporting
confidence: 93%
See 1 more Smart Citation
“…In winter, the correlation coefficients between AOD and PM 2.5 and AQI were the lowest, at 0.46 and 0.48, respectively. This result is consistent with the findings of many existing studies [34,60]. It also means that the correlation between AOD and AQI was higher than that of PM 2.5 in autumn and winter.…”
Section: Relationship Between Aod and Pm 25 /Aqisupporting
confidence: 93%
“…Many studies have shown that there is a correlation between AOD and PM 2.5 concentrations [30][31][32][33], and many scholars have estimated near-ground atmospheric particulate matter concentrations based on satellite remote sensing AOD products [34][35][36][37][38]. However, the correlation between AOD and PM 2.5 concentrations on a time scale with periodic characteristics is ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Because of error terms or extreme values from observation, local statistics can show bad performance. As indicated in Koo [47], the impact of hygroscopic growth factors on AOD can differ among observational locations. Further studies are required to address this issue.…”
Section: Springtimementioning
confidence: 99%
“…The exceedance of pollutants, such as particulate matter, nitrogen dioxide, and ozone, is a major challenge in terms of improving urban air quality [16][17][18][19]. Internationally, the development of AOD inversion algorithms [20][21][22][23][24], the spatiotemporal distribution of AOD and pollution characteristics [25][26][27][28][29][30], PM 2.5 estimation, and others [31][32][33][34][35][36] have been extensively investigated. Most importantly, a thorough understanding of the spatiotemporal distribution patterns of aerosols in various regions, over long time series, and the mechanism of their effects on air pollution and climate change is essential.…”
Section: Introductionmentioning
confidence: 99%